Cultural Transformation through Language Integration: An Interdisciplinary Approach: Cultural Transformation through Language Integration - Asna Andriani, Asna Andriani (Metafora: Education, Social Sciences and Humanities Journal, 2024)
Language is a key factor in the process of cultural change, especially in the context of a multicultural and globalised society. This article presents an in-depth analysis of how language integration affects cultural dynamics in society. It adopts an interdisciplinary approach combining linguistic, anthropological and sociological perspectives, focusing on several important aspects, including the notion of language integration, the relationship between language and culture, and the role of language as a tool of cultural integration. In addition, the article also explores the impact of language integration in a multicultural context, as well as the contribution of education and social media in the process. Thus, the article provides a comprehensive overview of the role of language in cultural transformation, demonstrating that language serves not only as a means of communication, but also as a significant agent of transformation in the formation, maintenance and change of cultural identity.